Analisis Potensi Bahaya Menggunakan Metode JSA dan HIRARC untuk Mengurangi Angka Kecelakaan Kerja pada Area Workshop Fabrikasi PT. ABC - Muhammad Ilyas Hamdani; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. ABC is a construction company because of the company's expertise in steel processing and construction. Activities such as welding, grinding, cutting and assembling are directly related to the work of these construction services. In this research, the (HIRARC) method was used to carry out risk analysis. The Job Safety Analysis (JSA) method is utilized to recognize stages of hazards. From the outcomes of identifying risk hazards, those linked with each task will be evaluated according to severity and likelihood levels to establish the risk level. This research indicates that in the welding process, there are 4 extreme risk hazards and 1 high-risk hazard. In the grinding process, there are 4 extreme risk hazards and 1 high-risk hazard. In the cutting process, there is 1 extreme risk hazard, 2 high-risk hazards, and 2 moderate-risk hazards. Lastly, in the assembling process, there is 1 extreme risk hazard, 1 high-risk hazard, 1 moderate-risk hazard, and 1 low-risk hazard.